Cultural Pregnancy in the Prevention of Prenatal Depression Based on Transcultural Nursing Theory in Pregnant Women - Abdul Aziz Azari; Dwi Indah Lestari; Ishana Balaputra (Poltekkes Kemenkes Tanjung Karang, 2025)
Cultural pregnancy practices in prenatal care encompass prohibitions on specific behaviors and dietary restrictions that reflect community concerns during pregnancy. These practices may also contribute to prenatal depression. This study seeks to analyze factors related to transcultural nursing theory and cultural pregnancy in preventing prenatal depression among pregnant women in Jember Regency, Indonesia. A descriptive analytical cross-sectional design with a non-proportional stratified random sampling technique was employed, involving 420 participants. Data were collected using a questionnaire based on the eight dimensions of Transcultural Nursing and Cultural Pregnancy theory. The data were analyzed using Spearman's rho test. The results revealed significant correlations among pregnancy culture, social support, economic status, educational background, and cultural beliefs. Technological factors, particularly access to health information, were associated with healthier pregnancy behaviors. Religious and spiritual engagement contributed to stronger coping mechanisms and reduced emotional distress. Family kinship and social interaction played a determining role in identifying and reducing harmful cultural practices. In conclusion, multidimensional cultural, social, technological, and spiritual factors significantly influence prenatal mental health. Strengthening family support, enhancing access to accurate information, and addressing restrictive or harmful cultural practices are essential strategies for preventing prenatal depression among pregnant individuals.